DAYA SAING PRODUK PERDAGANGAN INDONESIA PASCA KERJASAMA ASEAN-AUSTRALIA-NEW ZEALAND FTA - Eka Puspitawati; Putu Gayatri Anindhya Sari (Aliansi Perguruan Tinggi Badan Usaha Milik Negara (APERTI BUMN), 2019)
This study shows how Indonesian’s competitiveness of the main export commodities after the implementation of ASEAN-Australia New Zealand Free Trade Area (AANZFTA) is. Controversy whether a country will gain from trade liberalisation or not is proved by the results of this study. Using two analysis tools which are compared, Revealed Comparative Advantage (RCA) dan Normalized Revealed Comparative Advantage (NRCA), it is concluded that Indonesia gains from AANZFTA. The main commodities of Indonesia which have high competitiveness in the market of ASEAN and ANZ are oil and gas i.e, natural gas, petroleum oil and coal, and non-oil and gas i.e, crude palm oil and cigarette. Although it gains, it needs to be alert on the loss since there is a tendency of competitiveness decresence for Indonesian commodities in ASEAN and ANZ market. Indonesia is expected to do inovation and to develop sustainable products offering high competitiveness and value added in the fututre. Products related on sources of renewable energy are potentially recommended.